Approaches Toward Targeting Matrix Metalloproteases for Prognosis and Therapies in Gynecological Cancer: MicroRNAs as a Molecular Driver - Pandit, Anuradha; Begum, Yasmin; Saha, Priyanka; Srivastava, Amit Kumar; Swarnakar, Snehasikta (Frontiers in Oncology, 2022)
Gene expression can be regulated by small non-coding RNA molecules like microRNAs (miRNAs) which act as cellular mediators necessary for growth, differentiation, proliferation, apoptosis, and metabolism. miRNA deregulation is often observed in many human malignancies, acting both as tumor-promoting and suppressing, and their abnormal expression is linked to unrestrained cellular proliferation, metastasis, and perturbation in DNA damage as well as cell cycle. Matrix metalloproteinases (MMPs) have crucial roles in both growth, and tissue remodeling in normal conditions, as well as in promoting cancer development and metastasis. Herein, we outline an integrated interactive study involving various MMPs and miRNAs and also feature a way in which these communications impact malignant growth, movement, and metastasis. The present review emphasizes on important miRNAs that might impact gynecological cancer progression directly or indirectly via regulating MMPs. Additionally, we address the likely use of miRNA-mediated MMP regulation and their downstream signaling pathways towards the development of a potential treatment of gynecological cancers.